The variational theory of fracture: diffuse cohesive energy and elastic-plastic rupture - Riccardo March; Giovanni Lancioni; Gianpietro Del Piero (Fracture and Structural Integrity, 2011)
This communication anticipates some results of a work in progress [1], addressed to explore the efficiency of the diffuse cohesive energy model for describing the phenomena of fracture and yielding. A first local model is partially successful, but fails to reproduce the strain softening regime. A more robust non-local model, obtained by adding an energy term depending on the deformation gradient, describes many typical features of the inelastic response observed in experiments, including strain localization and necking. Fracture occurs as the result of extreme strain localization. The model predicts different fracture modes, brittle and ductile, depending on the analytical form of the cohesive energy function.